Linking coral river runoff proxies with climate variability, hydrology and land-use in Madagascar catchments - Maina, J.; de Moel, H.; Vermaat, J.; Bruggemann, J.; Guillaume, M.; Grove, C.; Madin, J.; Mertz-Kraus, R.; Zinke, Jens (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Understanding the linkages between coastal watersheds and adjacent coral reefs is expected to lead to better coral reef conservation strategies. Our study aims to examine the main predictors of environmental proxies recorded in near shore corals and therefore how linked near shore reefs are to the catchment physical processes. To achieve these, we developed models to simulate hydrology of two watersheds in Madagascar. We examined relationships between environmental proxies derived from massive Porites spp. coral cores (spectral luminescence and barium/calcium ratios), and corresponding time-series (1950–2006) data of hydrology, climate, land use and human population growth. Results suggest regional differences in the main environmental drivers of reef sedimentation: on annual time-scales, precipitation, river flow and sediment load explained the variability in coral proxies of river discharge for the northeast region, while El Niño-Southern Oscillation (ENSO) and temperature (air and sea surface) were the best predictors in the southwest region.